Aktualisasi Manusia Versi Al-Qur’an : Antara Idealitas dan Realitas Pendidikan Islam - Ismail Thoib (Universitas Islam Negeri Mataram, 2008)
Muslim must actualize values in the Qur’an in their life. So, the term Qur’anic actualization means total actions and comprehensive works colored by Qur’anic spirits either in their aims, strategies or implementation. This will lead Muslims to be khayra ummah (the best ummah). Allah entrusts them to be the one only heir of this world. Nowadays, Muslims have failed to be the world heir. We have failed to be masters of qawliyah verses written in the Al-Qur’an and of kawniyah verses manifested in this wide world. Many factors are considered causes of the failure. The prime factor is education. Education developed in Muslim communities has not totally referred to Qur’anic frameworks. Illiteracy, meaninglessness, paradigm confusion and disorientation still paint implementation of Islamic education. Muslims will revive to be the best ummah if only Islamic education, both its theories and praxes, is constructed by basing on Qur’anic vision and mission.